استخدام عتبة المردودية في زيادة إنتاجية المؤسسة الاقتصادية - عائشـــــــــــــــــــــة, علية; زكريا, قيطوبي; زهر الدين, النوي (unuversity of eloued- جامعة الوادي, 2023)
"المقدمة: يعتبر الربح هو الهدف الأساسي لكل المؤسسات الاقتصادية، والتزايد في الأرباح من السنة إلى أخرى هو النتيجة الآلية لزيادة الإنتاجية في هذه المؤسسات، إلا أن قياس زيادة الإنتاجية يكون إلا من خلال عتبة المردودية المخطط الوصول إليها؛ وهو موضوع هذا البحث المتواضع الذي نلخصه في الآتي: المؤسسة الاقتصادية: هي كيان معنوي هدفه إحداث قيمة مضافة للفرد أو المجتمع، وذلك من خلال توفير كل ما يحتاجه الفاعلين فيها والمرتبطين بها، أي الوصول إلى درجة إشباع الرغبات المتزايدة والمتعددة لهم. الإنتاجية: هي الجهد العملي أو الفكري أو التقني أو الإبداعي الذي يبذله الفرد أو المجموعة من أجل الحصول على مقابل المادي متمثل في الأجور أو الرواتب أو أرباح، ومقابل معنوي متمثل في الحوافز أو المكافآت أو الترقيات، في حيز مكاني متمثل محدد في المؤسسة الاقتصادية بكل أنواعها وتسمياتها. التحليل المالي: هو العلم الذي يدرس كل ما يخص العمليات المالية التي تخص المؤسسات الاقتصادية، حتى تتمكن هذه الأخيرة من اتخاذ القرارات المناسبة في الوقت والمكان المناسب، فهو يستفيد من كل التحركات المالية التي تتم داخل أو خارج هذه المؤسسات، في عملية تحليله للأحداث ووضعه للخطط التي تتمثل الاستراتيجيات المستقبلية والخطط التشغيلية والتي يجب تحقيقها في آجال معينة بما يتماشى مع رؤية ورسالة هذه المؤسسات. المردودية: هي الهدف الذي تسعى المؤسسات للحصول عليه من خلال، مزاولتها لهذا النشاط الاقتصادي أو ذاك، وهي إحدى الأسباب المؤدية إلى الربح أو الخسارة في المؤسسة الاقتصادية، ومن أجل وضع قواعد تضبط المردودية، يتم وضع عتبة لهذه المردودية لتحديد إنتاجيتها ونجاحها، من خلال النتيجة الصافية الموجبة. الإنتاجية: إذا كانت المردودية تهتم بالجانب المالي المحاسبي على العموم فهي تعتمد على الأرقام والإحصائيات، والجداول والميزانيات في عملياتها، فإن الإنتاجية تهتم بالقيمة المضافة في العمل والابداع والابتكار دخل المؤسسة الاقتصادية فهي تهتم بكل ما من شأنه تحسين الأداء الإنتاجي. الاستراتيجيات المستقبلية للمؤسسات الاقتصادية: تعتمد على محاولة وضع مقاربات آلية ولوضع نفطة تقاطع بين المردودية المالية والإنتاجية الاقتصادية من خلال وضع بعض النسب التي تحاول قياس مدى تأثير وضع عتبة للمردودية لتحفيز الزيادة في الإنتاجية ضمن ظروف داخلية وخارجية المتعددة ومتداخلة للمؤسسة الاقتصادية الهادفة في مبدأها إلى الربح المالي أولاً، ثم الاجتماعي والاقتصادي والسياسي وفي المحيط النقابي والبيئي...إلخ. " "Introduction: Profit is the primary goal of all economic institutions, and the increase in profits from one year to another is the automatic result of increased productivity in these institutions. However, the measurement of increased productivity can only be through the threshold of returns that are planned to be reached. This is the subject of this modest research, which we summarize as follows: Economic institution: It is a moral entity whose goal is to create added value for the individual or society, by providing everything needed by its actors and those associated with it, that is, reaching the degree of satisfaction of their increasing and multiple desires. Productivity: It is the practical, intellectual, technical, or creative effort made by an individual or group in order to obtain material compensation, represented by wages, salaries, or profits, and moral compensation, represented by incentives, rewards, or promotions, in a specific spatial space represented in the economic institution of all kinds. And its nomenclature. Financial analysis: It is the science that studies everything related to the financial operations of economic institutions, so that the latter can make the appropriate decisions at the appropriate time and place. It benefits from all financial movements that take place inside or outside these institutions, in the process of analyzing events and developing plans. Which represent future strategies and operational plans that must be achieved within certain deadlines in line with the vision and mission of these institutions. Yield: It is the goal that institutions seek to obtain through their practice of this or that economic activity, and it is one of the reasons leading to profit or loss in the economic institution. In order to establish rules that control the return, a threshold for this return is set to determine its productivity and success, through the result. Net positive. Productivity: If productivity is concerned with the financial aspect of accounting in general, it depends on numbers, statistics, tables and budgets in its operations. Productivity is concerned with the value added in work, creativity and innovation entering the economic institution, as it is concerned with everything that improves productive performance. Future strategies for economic institutions: depend on an attempt to develop automated approaches and to establish an intersection between financial returns and economic productivity by establishing some ratios that attempt to measure the extent of the impact of setting a threshold for returns to stimulate an increase in productivity within the multiple and overlapping internal and external conditions of the economic institution that aims, in principle, for financial profit. First, then the social, economic, political, trade union, environmental, etc "
Keywords: المردودية، عتبة المردودية، الإنتاجية، المؤسسة الاقتصادية، التحليل المالي، النسب المالية، النتيجة الصافية، الاستراتيجيات المستقبلية، الأرباح.; return, return threshold, productivity, economic institution, financial analysis, financial ratios, net result, future strategies, profits.